(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Broadly speaking, this research discusses the economic policies of Britain during Margaret Thatcher’s tenure from 1979 to 1990. The gradual and steady sequence of events filling the dynamics of the British economy compelled Margaret Thatcher to devise a long-term plan regarding economic policies. This study aims to provide an understanding of Margaret Thatcher’s struggles in dealing with the economic turmoil in Britain from 1979 to 1990. The method employed is historical, involving four steps: heuristic, criticism, interpretation, and historiography. According to the research findings, Thatcher’s background in implementing free market policies was aimed at reforming the British economy. Thatcher made several efforts to bring about changes that were perceived as beneficial for the economy of Britain. Ultimately, Thatcher’s measures had both positive and negative impacts on various social and economic strata.